Archives Alive!: librarian-faculty collaboration and an alternative to the five-page paper - Tom Keegan; Kelly McElroy (In the Library with the Lead Pipe, 2015)
In brief: The short research paper is ubiquitous in undergraduate liberal arts education. But is this assignment type an effective way to assess student learning or writing skills? We argue that it rarely is, and instead serves as an artifact maintained out of instructor familiarity with and unnecessary allegiance to timeworn conceptions of “academia.” As […]